2004
DOI: 10.1007/s00417-003-0844-0
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of visual acuity with photodynamic therapy in eyes with chorioretinal anastomoses

Abstract: The natural history of AMD eyes with CRA leads to progressive and dramatic VA loss, which is associated with blindness in most of the cases. PDT with verteporfin can offer some benefit to these patients, allowing VA stabilization or improvement in more than two thirds of the cases, at one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…Reviewing our experience with PDT in 13 eyes with ARMD with RAP and PED, we found it effective for small lesions, whereas it was associated with an acute retinal pigment epithelium tear in three cases (23%) [4]. In view of the uncertainties in the treatment of RAP [2,19], we evaluated the efficacy of PDT using verteporfin in patients with ARMD and RAP associated with PED and/or CNVs on a larger number of eyes with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Reviewing our experience with PDT in 13 eyes with ARMD with RAP and PED, we found it effective for small lesions, whereas it was associated with an acute retinal pigment epithelium tear in three cases (23%) [4]. In view of the uncertainties in the treatment of RAP [2,19], we evaluated the efficacy of PDT using verteporfin in patients with ARMD and RAP associated with PED and/or CNVs on a larger number of eyes with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the five lesions exceeding six disc areas had a bad anatomical and visual outcome. Silva and co-authors [19] found stabilization of visual acuity (VA) with PDT in eyes with chorioretinal anastomosis, offering some benefit in comparison with the natural course of the disease. Similar to our results, they reported BCVA loss of more than three lines in 35.3%, and severe VA loss in 20% of the eyes, with a worse prognosis for eyes with larger PED.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Over the past years, the success rate of the various available treatments has been inconsistent. Nevertheless, some authors report relative stabilization of the disease with treatment, either PDT [13,14] or IV ranibizumab [18,19,21]. PDT was combined with IV ranibizumab [18,24] or even IV triamcinolone [18].…”
Section: Discussionmentioning
confidence: 99%
“…While several treatment approaches proved unsuccessful in the past [13,14,15,16,17], the blockage of vascular endothelium growth factor (VEGF) has substantially changed the prognosis of this condition. Reports on intravitreal (IV) ranibizumab, either in monotherapy or with concomitant photodynamic therapy (PDT), have underlined the responsiveness of RAP lesions to both treatment modalities [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%